Evaluation of the Usefulness of Virtual Chromoendoscopy with Different Color Modes in the MiroCam® System for Characterization of Small Bowel Lesions - Silva,Joana Ribeiro da (2018)
Background: Virtual chromoendoscopy (VC) in small bowel capsule endoscopy can improve the visualization and characterization of different small bowel lesions (SBLs). There are few studies of its usefulness in the Given® system, and there is no evidence yet of its utility in the MiroCam® system. Aim: The aim of this study was to evaluate whether VC can improve the characterization of SBLs with the MiroCam® system. Methods: Twenty-two patients were selected, in which 100 elementary lesions were identified, including erosions (n = 45), ulcers (n = 17), and angioectasias (n = 38). For each lesion identified, images were captured without chromoendoscopy (normal image [NI]) and with chromoendoscopy modes 1 (color mode [CM] 1), 2 (CM2), and 3 (CM3). A score from 1 to 4 was assigned to each image, in which a better evaluation of the characteristics and limits of the lesion was classified in ascending order, where 1 is the worst and 4 the best evaluation. The scores of the various modes were compared with Kendalls tau-c coefficient. Results: The average scores attributed to the photographs in NI, CM1, CM2, and CM3 were 3.83, 2.89, 1.85, and 1.43, respectively (tau-c = -0.75, p < 0.001). Evaluating the elementary lesions independently, the average scores for modes NI, CM1, CM2, and CM3 were 3.83, 2.92, 1.86, and 1.38 (tau-c = -0.77, p < 0.001) for erosions, respectively; 3.87, 2.96, 1.76, and 1.40 (tau-c = -0.80, p < 0.001) for ulcers, respectively; and 3.81, 2.82, 1.87, and 1.50 (tau-c = -0.71, p < 0.001) for angioectasias, respectively. Conclusions: VC using the CMs available in the Miro-Cam® system has not proven useful for a better assessment of any of the SBLs.